Conceptual and empirical advances in Neotropical biodiversity research - Antonelli A; Ariza M; Albert J; Andermann T; Azevedo J; Bacon C; Faurby S; Guedes T; Hoorn C; Lohmann L; Matos-Maraví P; Ritter C; et al. (PeerJ, Ltd., 2022)
The outstanding biodiversity found in the American tropics (the Neotropics) has attracted the attention of naturalists for centuries. Despite major advances in the generation of biodiversity data, many questions remain to be answered. In this review, we first summarize some of the knowns and unknowns about Neotropical biodiversity, and discuss how human impact may have drastically affected some of the patterns observed today. We then link biodiversity to landscape, and outline major advances in biogeographical research. In particular, we argue that it is crucial to test the effect of landscape and climatic evolution to biotic diversification and distribution in order to achieve a comprehensive understanding of current patterns. In this context, it is also important to consider extant and extinct taxa, as well as to use probabilistic and parametric methods that explicitly include landscape evolution models. We subsequently explore different scales in Neotropical biogeography, focusing on the intersection between biogeography and community ecology, both of which often address similar questions from different angles. The concepts of community assembly, island biogeography, neutral processes, and ecological interactions are then discussed as important components of the complex processes that determine the patterns observed today. Single-taxon and cross-taxonomic studies are complementary and greatly needed, but achieving synthesis remains challenging. Finally, we argue that phylogenetic approaches hold great potential to connect across taxonomic, spatial and temporal scales, despite current difficulties to generate and cross-analyze large volumes of molecular data. We conclude by outlining major prospects and hindrances for further advancing our knowledge on the rich Neotropical biodiversity.